2014
DOI: 10.1016/j.cmet.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Low Protein Intake Is Associated with a Major Reduction in IGF-1, Cancer, and Overall Mortality in the 65 and Younger but Not Older Population

Abstract: Summary Mice and humans with Growth Hormone Receptor/IGF-1 deficiencies display major reductions in age-related diseases. Because protein restriction reduces GHR-IGF-1 activity, we examined links between protein intake and mortality. Respondents (n=6,381) aged 50–65 reporting high protein intake had a 75% increase in overall mortality and a 4-fold increase in cancer and diabetes mortality during an 18 year follow up period. These associations were either abolished or attenuated if the source of proteins was pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
659
2
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(723 citation statements)
references
References 79 publications
18
659
2
16
Order By: Relevance
“…However, it is still unclear whether the effects of dietary manipulation persist in very old organisms. An observational study in humans has shown that low protein intake during middle age (50–65 years) is associated with major reductions in cancer prevalence and overall mortality, while higher protein intake is associated with the opposite outcomes in populations over 65 years (Levine et al., 2014). These results indicate that dietary regimens do not affect healthy lifespan in the same way throughout life, and therefore, the diet should be modified according to age to maximize healthy lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether the effects of dietary manipulation persist in very old organisms. An observational study in humans has shown that low protein intake during middle age (50–65 years) is associated with major reductions in cancer prevalence and overall mortality, while higher protein intake is associated with the opposite outcomes in populations over 65 years (Levine et al., 2014). These results indicate that dietary regimens do not affect healthy lifespan in the same way throughout life, and therefore, the diet should be modified according to age to maximize healthy lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…It seems unlikely, however, that IGF-I's impact on the vasculature played an important role in the lower mortality associated with higher protein intakes among the elderly in the NHANES III analysis, as, among those over 65, plasma IGF-I levels did not differ significantly as a function of protein intake (Levine et al 2014). However, IGF-I did moderate the association between protein intake and cardiovascular risk-for those over 65, a higher protein intake predicted reduced cardiovascular risk only in those whose IGF-I levels were relatively low.…”
mentioning
confidence: 98%
“…Hence, greater cysteine availability may explain much of the favorable impact of higher protein intakes on mortality and frailty risk in the elderly, and joint supplementation with NAC and lipoic acid could be notably protective in the elderly, particularly in those who follow plant-based diets relatively low in protein. It is less clear whether the A recent analysis of the National Health and Nutrition Examination Survey (NHANES) III prospective cohort study, focusing on the association between protein intake at baseline and subsequent health outcomes in subjects over 50, found that a relatively low protein intake (under 10 % of calories) in subjects between 50 and 65 correlated with lower overall mortality, including decreased mortality from cancer and diabetes (Levine et al 2014). In contrast, among subjects over 65 at baseline, such a low protein intake was associated with increased risk for overall and cancer-linked mortality.…”
mentioning
confidence: 99%
“…Barnard (1991) found that patients who switched to a mostly vegetable diet (one cold cut of meat per day was allowed) were able to lower their insulin medications by an average of 40% (Type I diabetes patients) or were completely able to discontinue their insulin medication (Type II patients). More recently, researchers have shown that diets high in protein (mainly from animal sources) increase middleaged individuals' risk of cancer to four times that of individuals who consume low amounts of protein from animal sources (Levine et al, 2014). From these results one would conclude that there are externalities imposed upon society by the production of meat and dairy products in the sense that consumers are provided potentially unhealthy products that contribute to the perpetuation of heart disease, diabetes, and other diseases of affluence.…”
Section: Stated Thatmentioning
confidence: 79%